1999
DOI: 10.1002/pen.11623
|View full text |Cite
|
Sign up to set email alerts
|

On‐line measurement of orientation development in the high‐speed melt spinning process

Abstract: On‐line measurement of birefringence was performed in the high‐speed melt spinning process of poly(ethylene terephthalate) using an apparatus that incorporates a rotating polarizer for the measurement of the optical retardation of running filament. Particular attention was paid to the detailed measurements in the vicinity of neck‐like deformation. Through the measurement at the take‐up velocity of 5 km/min, development of birefringence under the strain rate up to about 1 ms−1 was investigated. To analyze the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…reported the development of molecular orientation before the neck-like deformation, which they analyzed by on-line birefringence measurement using a rotating polarizer 3 . Hirahata et al's study, falling under the latter category, reports observation of weak crystal reflections before neck-like deformation by wide-angle x-ray diffraction (WAXD) measurement for high-speed spin-line of PET fiber 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported the development of molecular orientation before the neck-like deformation, which they analyzed by on-line birefringence measurement using a rotating polarizer 3 . Hirahata et al's study, falling under the latter category, reports observation of weak crystal reflections before neck-like deformation by wide-angle x-ray diffraction (WAXD) measurement for high-speed spin-line of PET fiber 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7]37,38 , and x-ray diffraction measurement for direct observation of fiber structure development . Studies falling under the former category have revealed that crystallization after necking causes a temperature increase 2,37 .…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, however, the velocity kept increasing smoothly and became close to the take-up velocity at the lower limit of the region for the velocity measurement. Cooling behavior of the spinline can be roughly estimated knowing the throughput rate, extrusion temperature and specific heat of the polymer, and empirically it can be said that the temperature of the spinline reaches to the ambient temperature within 150 cm down from the spinneret under the spinning conditions adopted in this ex- periment [13]. This consideration suggests that the deformation of the spinline continues even after the spinline temperature reaches the ambient temperature.…”
Section: On-line Velocity Profilementioning
confidence: 98%
“…In melt spinning, on-line measurements of fiber diameters have been developed by the existing commercial measurement devices. Kikutani et al 4 developed a diameter measurement system by three diameter monitors, enabling us to measure the movement of diameter profiles based on the back-illumination principle. The monitors provided a noncontact technique for accurate measurement of diameters within 2 mm in the spinline velocity of 10,000 m/min.…”
Section: Introductionmentioning
confidence: 99%